Mechanisms of current fluctuation in ambipolar black phosphorus field-effect transistors. Issue 6 (25th January 2016) - Li, Xuefei; Du, Yuchen; Si, Mengwei; Yang, Lingming; Li, Sichao; Li, Tiaoyang; Xiong, Xiong; Ye, Peide; Wu, Yanqing
Abstract : We provide the first systematically studied on the carrier transport properties and the low frequency noise mechanisms from 300 to 20 K in the BP ambipolar transistor. Abstract : Multi-layer black phosphorus has emerged as a strong candidate owing to its high carrier mobility with most of the previous research work focused on its p-type properties. Very few studies have been performed on its n-type electronic characteristics which are important not only for the complementary operation for logic, but also crucial for understanding the carrier transport through the metal–black phosphorus junction. A thorough understanding and proper evaluation of the performance potential of both p- and n-types are highly desirable. In this paper, we investigate the temperature dependent ambipolar operation of both electron and hole transport from 300 K to 20 K. On-currents as high as 85 μA μm −1 for a 0.2 μm channel length BP nFET at 300 K are observed. Moreover, we provide the first systematic study on the low frequency noise mechanisms for both n-channel and p-channel BP transistors. The dominated noise mechanisms of the multi-layer BP nFET and pFET are mobility fluctuation and carrier number fluctuations with correlated mobility fluctuations, respectively. We have also established a baseline of the low electrical noise of 8.1 × 10 −9 μm 2 Hz −1 at 10 Hz at room temperature for BP pFETs, which is 3 times improvement over previous reports, and 7.0 × 10 −8 μm 2 Hz −1 for BP nFETs for the first time.